Photobiological and Biochemical Characterization of Conchocelis and Blade Phases from Porphyra linearis (Rhodophyta, Bangiales) - Débora Tomazi Pereira; Félix L. Figueroa (Phycology)
Porphyra specimens are red macroalgae with significant economic importance for food and pharmaceutical industries due to their physiological activities resulting from their bioactive compounds (BACs). Due to its economic importance, this research aimed to characterize the photosynthetic and biochemical aspects of the conchocelis and blade phases of Porphyra linearis to understand and help improve production of this algae. The algae were cultured for 7 days with nutrients for blade phase measurements, while another portion was cultured without nutrients for 21 days to release carpospores, which were cultivated for 4 months. For both phases, the content of BACs (chlorophyll a, carotenoids, phycobiliproteins, phenols, carbohydrates, proteins, mycosporine-like amino acids), antioxidant activity, and photosynthetic parameters were analyzed. Most of the parameters showed the blade phase had better results than conchocelis, except for carbohydrates. Phycobiliproteins showed no statistical differences between the phases. These findings highlight that conchocelis is not a good BACs source compared to the blade phase, but it is a crucial phase in the life cycle of Porphyra. Understanding the key parameters for maintaining the cultivation of conchocelis stocks for the development of the blade phase is a way to produce macroscopic biomass of this economically important algae throughout the year.